EFL STUDENTS’ VOICES ON LEARNING VOCABULARY THROUGH THE USE OF DOODLES INSTAGRAM ACCOUNT - Waridatul Hikmah; Asfi Aniuranti; Wulandari Yasinta (Economics, Social, and Humanities Journal (Esochum), 2022)
Students’ perceptions are essential elements in the EFL context. Therefore, there are many studies related to students’ voices conducted. This research objective was to investigate students’ opinions on Doodles Instagram Account as a learning medium of English vocabulary. This research was a descriptive qualitative study. The participants of this research were 27 students in the ELT Department of Universitas Nahdlatul Ulama Purwokerto. After the students learned English vocabulary through several relevant posts taken from @doodles account, the team asked the students to complete a questionnaire. The questionnaire was a closed questionnaire consisting of 22 questions. The data obtained were analyzed by calculating the percentage of each item. The results revealed several essential findings. Firstly, most of the students were active users of Instagram. Secondly, the students mostly used Instagram to enrich their English vocabulary. Thirdly, the students generally responded positively to Doodle Instagram Account. Overall, the students’ voices toward @doodles account as a learning medium of English vocabulary tended to be positive.